Utilization of POME waste as a renewable energy source in the life cycle concept of palm oil biodiesel - Paminto, Ari Kabul (Journal of Earth Kingdom, 2025)
Background: In 2024, Indonesia, an importer of crude oil and fuel, is shifting focus to renewable energy as fossil fuel production declines. This research aims to develop a life cycle concept for biodiesel production from palm oil, addressing environmental concerns related to emissions from FFB, CPO, and biodiesel production processes. Methods: The method used in this research is a combination of quantitative LCA (Life Cycle Assessment) and AHP (Analytical Hierarchy Process) along with qualitative methods. Findings:  This research identifies and evaluates the alternative utilization of Palm Oil Mill Effluent (POME) waste with certain priority weights. The results showed that biodiesel production from palm oil requires various significant inputs, such as NPK fertilizer, herbicides, water, diesel, and Crude Palm Oil (CPO), resulting in environmental emissions in the form of CO2 of 1489 Kg CO2 (eq) per ton of biodiesel, as well as contributions to eutrophication and acidification. The LCI (Life Cycle Inventory) analysis also identified that the largest CO2 emissions came from POME waste (53%), followed by NPK fertilizer (23%), methanol (18%), and diesel oil (7%), while eutrophication and acidification indicated significant contributions from NPK fertilizer, methanol, diesel oil, and POME waste. These findings confirm the importance of utilizing POME waste as an optimal step to reduce CO2 emissions with a potential reduction of up to 667.2 Kg CO2 through a more sustainable biodiesel production life cycle concept. Conclusion: From this result, researchers recommend that palm oil companies start replacing chemical fertilizers with organic fertilizers to reduce environmental impacts, and encourage the utilization of POME waste at Palm Oil Mills as a source of biogas for renewable energy. At the biodiesel industry level, increasing the methanol recycling rate is proposed to improve efficiency and reduce emissions at the downstream stage of biodiesel production. Novelty/Originality of this article: This study identifies and evaluates alternatives for utilizing Palm Oil Mill Effluent (POME) waste with certain priority weights.